Gender differences in co-rumination and transition shock among nursing interns in China: a cross-sectional study - Wen-Jie Ge; Shou-Jun Zhu; Xin-Yi Zhu; Ai-Qin Chu (BMC Nursing)
Abstract Background It has been reported that co-rumination and transition shocks significantly influence effective communication in clinical practice. However, previous research has not sufficiently explored the specific relationships between these two characteristics and their gender differences among nursing interns. Objective The objective of this study was to evaluate the states of co-rumination and transition shock among current nursing interns during clinical placements, as well as to determine whether gender differences affect these two traits and how exploiting such differences can improve nurses’ co-rumination. Methods A cross-sectional study design was adopted. We gathered data from a convenient sample of 505 nursing interns from a grade A tertiary hospital in Anhui, China. This study included Data collected using the Co-Rumination Questionnaire (CRQ-9) and Transition Shock Scale for Undergraduate Nursing Students (UNSTS). The data were analyzed using an independent samples t-test, Pearson correlation, and hierarchical multiple linear regression. Results There was no significant difference in UNSTS scores between male and female nursing interns, but male nursing interns had lower CRQ-9 scores (P < 0.05). This study found that Transition Shock was the most critical factor influencing Co-Rumination variation for male and female nursing interns during clinical practice through hierarchical multiple regression analysis. Conclusions Gender differences are reflected not only in the level of co-rumination but also in the relationships between co-rumination and transition shock. Nursing educators should be aware of how gender differences can affect these two traits; this is particularly important for improving the mental health problems of nursing interns based on students’ aptitudes.